Mass screening for coeliac disease using antihuman transglutaminase antibody assay. Issue 6 (21st May 2004) - Tommasini, A; Not, T; Kiren, V; Baldas, V; Santon, D; Trevisiol, C; Berti, I; Neri, E; Gerarduzzi, T; Bruno, I; Lenhardt, A; Zamuner, E; et al.
Abstract : Aims: To determine coeliac disease prevalence by an anti-transglutaminase antibody assay in a large paediatric population; to evaluate acceptance of the screening programme, dietary compliance, and long term health effects. Methods: Cross-sectional survey of 3188 schoolchildren (aged 6–12) and prospective follow up of diagnosed cases. Main outcome measures were: prevalence of coeliac disease defined by intestinal biopsy or positivity to both human tissue transglutaminase and anti-endomysium antibodies in HLA DQ2-8 positive subjects; percentage of children whose families accepted screening; dietary compliance as defined by negativity for anti-transglutaminase antibodies; and presence of clinical or laboratory abnormalities at 24 month follow up. Results: The families of 3188/3665 children gave their consent (87%). Thirty biopsy proven coeliacs were identified (prevalence 1:106). Three other children testing positive for both coeliac related autoantibodies and HLA DQ2-8 but refusing biopsy were considered as having coeliac disease (prevalence 1:96). Of 33 cases, 12 had coeliac related symptoms. The 30 biopsy proven coeliacs followed a gluten-free diet. Of 28 subjects completing 18–24 months follow up, 20 (71.4%) were negative for anti-transglutaminase antibodies, while eight were slightly positive; symptoms resolved in all 12 symptomatic children. Conclusions: Prevalence of coeliac disease is high in Italian schoolchildren. Two thirds of cases were asymptomatic. Acceptance of the programme was good, as was dietary compliance. Given the high prevalence and possible complications of untreated coeliac disease, the availability of a valid screening method, and evidence of willingness to comply with dietary treatment population mass screening deserves careful consideration.